Left bundle branch pacing preserved left ventricular myocardial work in patients with bradycardia - Chen, Huang-Chung; Liu, Wen-Hao; Chen, Yung-Lung; Lee, Wei-Chieh; Fang, Yen-Nan; Chong, Shaur-Zheng; Chen, Mien-Cheng (Frontiers in Cardiovascular Medicine, 2023)
Background Left bundle branch pacing (LBBP) is an emerging physiological pacing modality. Left ventricular (LV) myocardial work (MW) incorporates afterload and LV global longitudinal strain to estimate global and segmental myocardial contractility. However, the effect of LBBP on LV MW remains unknown. This study aimed to evaluate the impact of LBBP on LV MW in patients receiving pacemaker for bradyarrhythmia. Methods We prospectively enrolled 70 bradycardia patients with normal LV systolic function receiving LBBP (n = 46) and non-selective His-bundle pacing (NS-HBP) (n = 24). For comparative analysis, patients receiving right ventricular pacing (RVP) (n = 16) and control subjects (n = 10) were enrolled. Two-dimensional speckle tracking echocardiography was performed. The LV pressure-strain loop was non-invasively constructed to assess global LV MW. Results After 6-month follow-up, LBBP group (with >40% ventricular pacing during 6 months) had shorter peak strain dispersion (PSD) compared with RVP group, and higher LV global longitudinal strain compared with RVP group and NS-HBP group, but had no difference in left intraventricular mechanical dyssynchrony, including septal-to-posterior wall motion delay and PSD, compared with NS-HBP group. During ventricular pacing, LBBP group had higher global MW index (GWI) (2,189 ± 527 vs. 1,493 ± 799 mmHg%, P = 0.002), higher global constructive work (GCW) (2,921 ± 771 vs. 2,203 ± 866 mmHg%, P = 0.009), lower global wasted work (GWW) (211 ± 161 vs. 484 ± 281 mmHg%, P < 0.001) and higher global MW efficiency (GWE) (91.4 ± 5.0 vs. 80.9 ± 8.3%, P < 0.001) compared with RVP group, and had lower GWW (211 ± 161 vs. 406 ± 234 mmHg%, P < 0.001) and higher GWE (91.4 ± 5.0 vs. 86.4 ± 8.1%, P < 0.001) compared with NS-HBP group. Conclusions In this study we found that in patients with mid-term (6-month) high ventricular pacing burden (>40%), LBBP preserved more LV MW compared with NS-HBP and RVP. Further studies are warranted to assess the association between LV MW and long-term clinical outcomes in LBBP with high ventricular pacing burden.